Analisis Faktor-Faktor yang Mempengaruhi Impor Susu Sapi di Indonesia - Ni Putu Nanda Pramesti Nata Putri; Ni Luh Karmini (Jayapangus Press, 2023)
Milk is a product that is commonly consumed and is beneficial for all ages because of its complete and balanced nutritional content. The contribution of domestic cow's milk to national needs is still fulfilled from imports. Many things can affect the import of cow's milk. Therefore it is necessary to identify the factors that influence the import of cow's milk in Indonesia. The aim of this research is to analyze the effect of production, foreign exchange reserves and GDP per capita simultaneously on the amount of imported cow's milk in Indonesia in 1991-2020. Another objective is to analyze the effect of production, foreign exchange reserves, and GDP per capita as a share of the volume of imported cow's milk in Indonesia in 1991-2020. The analysis technique is using multiple linear regression analysis. Secondary data takes from 30 observations which consist of time series data. The results found from this study are that simultaneously the variables of production, foreign exchange reserves and GDP per capita have a significant effect on the volume of imports of Indonesian cow's milk. The production variable has a negative and partially insignificant effect on the amount of imported cow's milk in Indonesia, foreign exchange reserves have a positive and significant effect on the amount of imported cow's milk in Indonesia, while the variable GDP per capita has a positive and insignificant effect on the volume of imported cow's milk in Indonesia.